2018
DOI: 10.1038/s41598-018-30285-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic trapping measures the interaction between membrane-associated molecules

Abstract: How membrane proteins distribute and behave on the surface of cells depends on the molecules’ chemical potential. However, measuring this potential, and how it varies with protein-to-protein distance, has been challenging. Here, we present a method we call hydrodynamic trapping that can achieve this. Our method uses the focused liquid flow from a micropipette to locally accumulate molecules protruding above a lipid membrane. The chemical potential, as well as information about the dimensions of the studied mol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…However, it should be noted that the concentration of both CD43 and CD45 in the cell's glycocalyx is high, ~1,000 molecules/μm 2 each ( 8 , 63 ), and so interactions with neighboring proteins will cause CD45 to adopt a more upright position on the cell surface (Figure 2A ). Indeed, using Monte Carlo simulations, similar to those described in Junghans et al ( 62 ), we found that this effect would increase the effective height of CD45 by ~5 nm. Thus, the effective height depends not only on the total length of the protein, but also on other properties including flexibility and protein density.…”
Section: Hydrodynamic Trappingsupporting
confidence: 79%
See 4 more Smart Citations
“…However, it should be noted that the concentration of both CD43 and CD45 in the cell's glycocalyx is high, ~1,000 molecules/μm 2 each ( 8 , 63 ), and so interactions with neighboring proteins will cause CD45 to adopt a more upright position on the cell surface (Figure 2A ). Indeed, using Monte Carlo simulations, similar to those described in Junghans et al ( 62 ), we found that this effect would increase the effective height of CD45 by ~5 nm. Thus, the effective height depends not only on the total length of the protein, but also on other properties including flexibility and protein density.…”
Section: Hydrodynamic Trappingsupporting
confidence: 79%
“…The accumulation will also be affected by intermolecular interactions among the proteins. By relating the amount of accumulation to the trap strength at different positions it is possible to determine both the orientation as well as the intermolecular interactions from a single measurement ( 62 ).…”
Section: Hydrodynamic Trappingmentioning
confidence: 99%
See 3 more Smart Citations